Pneumatosis intestinalis presenting with a pneumoperitoneum in a patient with chronic bronchiectasis: a delayed diagnosis of superior mesenteric artery ischaemia. (5th August 2010) - Dawe, Nicholas; Akhtar, Sidrah
Abstract : We describe a case of pneumatosis intestinalis (PI) in a 69-year-old woman presenting to the surgical department with non-specific abdominal pain and a pneumoperitoneum. PI complicated by pneumoperitoneum was diagnosed on the basis of the characteristic clinical and abdominal CT findings, demonstrating a cystic gas pattern within the small bowel wall. In the context of resolving clinical findings, non-peritonitic abdomen and with no evidence of portal venous gas or perforation the patient was managed conservatively. The findings were considered benign and attributed to her chronic acquired bronchiectasis. Following recurrence of symptoms after several months, further imaging confirmed chronic mesenteric ischaemia (CMI) involving the superior mesenteric artery. Angioplasty was performed and symptoms resolved. PI is one of the few imaging signs to occur in CMI. PI presenting as a pneumoperitoneum is rare and may often lead to avoidable surgical intervention. However, no clear algorithm exists to guide surgical management.